The court and its critics : anti-court sentiments in early modern Italy - Ugolini, Paola, 1974- (University of Toronto Press, 2020)
"Anti-courtly discourse furnished a platform for discussing some of the most pressing questions of early modern Italian society. The court was the space that witnessed a new form of negotiation of identity and prestige, the definition of masculinity and of gender-specific roles, the birth of modern politics and of an ethics based on merit and on individual self-interest. The Court and Its Critics analyzes anti-courtly critiques using a wide variety of sources including manuals of courtliness, dialogues, satires, and plays, from the mid-fifteenth to the early seventeenth century. The book is structured around four key figures that embody different features of anti-courtly sentiments. The figure of the courtier shows that sentiments against the court were present even among those who apparently benefitted from such a system of power. The court lady allows an investigation of the intertwining between anti-courtliness and antifeminism. The satirist and the shepherd of pastoral dramas are investigated as attempts to fashion two different forms of a new self for the court intellectual."--